PEMBELAJARAN SAINS BERBASIS E-LEARNING DAN PENGARUHNYA TERHADAP SIKAP, MINAT, MOTIVASI, DAN PRESTASI BELAJAR SISWA BERKEBUTUHAN KHUSUS - B., Nurhayati; Hadis, Abd.; Miru, Alimuddin S. (Indonesian Journal of Educational Studies, 2010)
Abstract. E-Learning Based Science Instruction and its Effect on Attitudes, Interests, Motivation, and Achievement of Students with Special Needs. This research aims at producing a package of e-learning-based science instruction for students with special needs. The study employs research and development method consisting of three stages, namely (1) identification of learning needs, (2) development of strategies and instructional materials, and (3) evaluation and revision. Subjects for try-out were students in grade V Special Education School (SLB). The product of the study produced is a learning package called â€œE-learning-based Science Instruction Package for Students with Special Needs in South Sulawesi. The result of the limited field test shows a very good learning outcomes in terms of attitude, interest, motivation, and learning outcome. Abstrak. Pembelajaran Sains Berbasis E-learning dan Pengaruhnya Terhadap Sikap, Minat, Motivasi, dan Prestasi Belajar Siswa Berkebutuhan Khusus. Penelitian ini bertujuan menghasilkan paket pembelajaran sain berbasis e-learning bagi siswa berkebutuhan khusus. Penelitian didesain dengan penelitian pengembangan melalui (1) identifikasi kebutuhan pembelajaran, (2) pengembangan strategi dan bahan pembelajaran, dan (3) evaluasi dan revisi. Subjek uji coba adalah siswa kelas V SLB. Penelitian ini menghasilkan produk yang diberi nama â€œPaket Pembelajaran Sains Berbasis E-learning (PPSBE) untuk Siswa Berkebutuhan Khusus SLB/SDLB Sulawesi Selatanâ€. Hasil uji lapangan terbatas menunjukkan hasil sangat baik dalam aspek sikap, motivasi, minat, dan prestasi belajar. Kata kunci: pembelajaran sains, e-learning, siswa berkebutuhan khusus